2013
DOI: 10.1057/ejdr.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Access and the Performance of Micro and Small Enterprises: Evidence from West Africa

Abstract: Although it is widely accepted that electricity access is important for enterprise performance, the empirical evidence on the subject is mixed. In addition, evidence is scarce for micro and small enterprises operating in the informal sector. On the basis of a representative sample of informal firms in seven West African cities, we do not find evidence of a systematic, significant contribution of electricity access to enterprise performance. However, concentrating on a more homogeneous sample of tailors in Ouag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Moreover, the study finds that MSEs that are not constrained by credit benefit from electricity access, suggesting that credit might be a complementary factor for reaping the benefits from electricity access. Grimm, Hartwig, and Lay (2013) find no systematic evidence that electricity access increases the performance of MSEs. There is a clear and decisive positive impact on the clothing sector, which seems to be the most homogeneous sector.…”
Section: Evidence From Recent Research In Africamentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, the study finds that MSEs that are not constrained by credit benefit from electricity access, suggesting that credit might be a complementary factor for reaping the benefits from electricity access. Grimm, Hartwig, and Lay (2013) find no systematic evidence that electricity access increases the performance of MSEs. There is a clear and decisive positive impact on the clothing sector, which seems to be the most homogeneous sector.…”
Section: Evidence From Recent Research In Africamentioning
confidence: 77%
“…In rural Rwanda, Lenz et al (2017) demonstrate that the impacts of electricity on business activities are most visible in communities that already had thriving commerce before electrification. Similarly, based on a representative sample of informal firms in seven West African cities, Grimm, Hartwig, and Lay (2013) show that electricity access exerts a positive impact on micro and small enterprises (MSEs) in the highest profit quintile. This finding suggests that MSEs might have to pass a critical threshold to benefit from the positive effects of electricity access.…”
Section: Evidence From Recent Research In Africamentioning
confidence: 99%
“…But, from a medium-to long-term perspective, there is a strong imperative to invest in infrastructure. For example, in terms of the impact of electricity access on SMEs and informal workers, a study for seven West African cities found that impact varies by sector (Grimm et al 2013), contributing to the uptake of modern machinery and business operation in the case of informal tailors in Burkina Faso (Ibid., p.816).…”
Section: Taxes and Feesmentioning
confidence: 99%
“…For instance, Grimm, Hartwig, and Lay (2013) investigate the importance of electricity access among informal firms in seven African cities. They find that electricity access is not statistically significant for good performance.…”
Section: Indiamentioning
confidence: 99%